Mécanismes de pouvoir et de solidarité féminine - Gloria de los Ángeles Zarza Rondón (Nuevo mundo - Mundos Nuevos, 2015)
The present study is part of a broader investigation that has been aimed at addressing the main characteristics of the Hispanic population lived in the city of Cadiz between 1765 and 18401. In this article, we approach the feminine universe through the consulted documentary sources, trying to inquire about the role and the place that occupied the American Women in Cadiz eighteenth and early nineteenth centuries.